Minha jornada na educação: prática e aprendizagem Reflexões e Experiências de uma formação pedagógica - Gertrude, Antônia Lana de Azevedo (Brasil, 2024)
This Final Course Work (FCW) aims to address the importance of the pedagogical process in my educational training. It is essential to highlight that this work is justified by the fact that it combines experiences throughout the Pedagogy Degree Course offered by the National Plan for Training Teachers in Basic Education (PARFOR), mediated by the Federal University of Amazonas (UFAM). To achieve the objective, TFC uses autobiography. With this work, it is possible to conclude that there is a need to explore the intersection between practice and learning in education, emphasizing how practical experiences enrich the educational process